Markets in Higher Education
XIII, 355 p.
Keywords: This volume presents the most comprehensive international discussion of the role of markets in higher education ever published. It reflects on both the political and economic implications of the rising trend towards introducing market elements in higher education. The book draws together many leading international scholars in the economic and policy analysis of higher education to explore different theoretical perspectives and present new empirical evidence on market mechanisms in higher education in several Western countries. The authors present a dispassionate and ideologically neutral view of the advantages and disadvantages of the introduction of market-mechanisms in higher education and of its effects in terms of access, equity, quality of provision, student learning, research and scholarship, and so on. And they balance the performance of markets in higher education against the alternative of more, or a different kind of, governmental intervention.